Effect of α-lipoic acid on spatial memory and structural integrity of developing hippocampal neurons in rats subjected to sodium arsenite exposure - Dixit, Shilpi; Mehra, Raj D.; Dhar, Pushpa (Environmental toxicology and pharmacology, 2020)
•Developing hippocampus displays increased vulnerability towards environmental contaminants like iAs.•Arsenic-induced adverse effects also unveiled as functional deficits such as anxiety & impaired learning & memory.•Concurrent administration of ALA with iAs resulted in the restoration of various parameters substantially.•Like preservation of neuronal connectivity and spine density to near the control values.•ALA-induced protection shows its role as a neuroprotectant in ameliorating arsenic-induced developmental neurotoxicity. Exposure to arsenic has been reported to affect the nervous system in a number of ways. Various epidemiological studies suggest cognitive impairment in subjects following exposure to environmental arsenic. The goal of the present study was to determine if supplementation of exogenous α-lipoic acid (ALA) could ameliorate sodium arsenite (NaAsO2) induced adverse effects on learning and memory and synaptic connectivity in rat hippocampus. Accordingly, NaAsO2 alone (1.5/2.0 mg/kg bw) or NaAsO2 along with ALA (70 mg/kg bw) was administered by intraperitoneal (i.p.) route from postnatal day (PND) 4–17 to Wistar rat pups (experimental groups) and the Control groups received either distilled water or no treatment at all. After carrying out Elevated Plus Maze (EPM) and Morris Water Maze (MWM) test, the fresh brain tissues were collected on PND 18 and processed for Golgi Cox staining. Observations of MWM test revealed impaired learning and memory in iAs alone treated animals as against those co-exposed to iAs and ALA. In Golgi stained hippocampal sections of iAs alone treated animals, decreased dendritic arborization and reduced number of spines in pyramidal neurons (CA1) and granule cells (DG) was observed whereas neuronal morphology was preserved in the controls and ALA supplemented groups These observations are suggestive of beneficial effects of ALA on iAs induced effects on learning and memory as well as on hippocampal neuronal morphology.